The impact of domestic CSR on the internationalisation of emerging-market multinational enterprises: evidence from India - Shirodkar, Vikrant; Shete, Namita (Springer, 2022)
Emerging-market multinational enterprises (EMNEs) are, on the one hand, investing in both developed and developing countries aggressively. On the other hand, they are facing greater pressures from their home and host countries to operate in a socially responsible manner. In this paper, combining institutional theory with strategic perspectives on corporate social responsibility (CSR), we argue that EMNEs spending on CSR more intensively in their domestic context are likely to have a greater scope of internationalisation. We also argue that this effect decreases for government-owned EMNEs and increases when EMNEs target developed host markets or institutionally stronger emerging markets. Our data used to test our hypotheses are based on a sample of 686 Indian firms. Our findings provide support for most of our arguments, and we contribute to a greater understanding of the relationship between CSR and internationalisation.
Keywords: Corporate Social Responsibility; Internationalisation; Emerging Market; Multinational Enterprises; International Business; Liabilities of Origin